2019
DOI: 10.1103/physrevlett.123.170605
|View full text |Cite
|
Sign up to set email alerts
|

Unifying Paradigms of Quantum Refrigeration: A Universal and Attainable Bound on Cooling

Abstract: Cooling quantum systems is arguably one of the most important thermodynamic tasks connected to modern quantum technologies and an interesting question from a foundational perspective. It is thus of no surprise that many different theoretical cooling schemes have been proposed, differing in the assumed control paradigm and complexity, and operating either in a single cycle or in steady state limits. Working out bounds on quantum cooling has since been a highly context dependent task with multiple answers, with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 41 publications
1
53
0
Order By: Relevance
“…They represent simple models comprised by few qubits (or harmonic oscillators) or a single qutrit weakly interacting with thermal reservoirs at different temperatures. They are self-contained configurations, thus avoiding external sources of coherence and control, which may incur in non-trivial thermodynamic costs [20,37] (for a comparison see [38,39]). Proposals for their implementation in the laboratory include quantum-dot models [40,41], a setup with ions in optical cavities [42] or in circuit QED architectures [43,44].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They represent simple models comprised by few qubits (or harmonic oscillators) or a single qutrit weakly interacting with thermal reservoirs at different temperatures. They are self-contained configurations, thus avoiding external sources of coherence and control, which may incur in non-trivial thermodynamic costs [20,37] (for a comparison see [38,39]). Proposals for their implementation in the laboratory include quantum-dot models [40,41], a setup with ions in optical cavities [42] or in circuit QED architectures [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…The performance of autonomous quantum refrigerators has been extensively studied in most prototypical configurations [24][25][26][30][31][32], in some of which the presence of steady-state entanglement [27] and quantum discord [31] has been found for particular regimes of parameters. Nevertheless, in these refrigerators, the ability to cool is limited by design constraints like the Hilbert space dimension of the machine [28] or the maximum energy gap in the machine Hamiltonian [38,39], and to be surpassed extra resources are needed. In particular, it has been shown that when replacing one of the thermal reservoirs by a squeezed thermal reservoir (or other nonthermal reservoirs) both the cooling power and the efficiency can be greatly improved [32,36] (see also [45]).…”
Section: Introductionmentioning
confidence: 99%
“…To formulate our ideas we adopt a commonplace view in quantum thermodynamics, namely, that work is a central resource that is required to move systems away from freely available thermal equilibrium states [24]-an approach that has staged a diverse range of investigations within the broader field [25][26][27]. In this paradigm, previous research has investigated the work-cost (or gain) of quantum processes [28][29][30][31][32], refrigeration [33,34], or for establishing correlations [35][36][37][38].…”
Section: Tpm Schemementioning
confidence: 99%
“…In particular, it was shown in [14] that ideal projective measurements are not exactly realisable in practise because they require the preparation of initially pure pointer states (at least in some nontrivial subspace) to satisfy condition (ii). However, the third law of thermodynamics prevents one from reaching the ground-state of any system with finite resources [15,33,34,[39][40][41][42]. Since any other (pure) state necessarily has higher energy than the ground state, the third law thus excludes ideal measurements.…”
Section: Ideal Measurementsmentioning
confidence: 99%
See 1 more Smart Citation